Superficial peroneal nerve accessory artery (SPNAA) flap for head and neck reconstruction: A cadaveric anatomical study and retrospective case series review. Issue 7 (July 2021) - Stocco, Chiara; Murphy, Declan C.; Gargiulo, Maurizio; Marasca, Dario; Figus, Andrea; Razzano, Sergio
Summary: Background: Several different flaps can reconstruct intraoral defects or lower limb deficits after free fibula osteo-cutaneous flap harvesting for jaw reconstructions. However, commonly used options may not be available for various reasons and can be associated with significant morbidity. We hypothesized that flaps supplied by the superficial peroneal nerve accessory artery (SPNAA) could be a viable alternative reconstructive option. Methods: We describe the SPNAA's anatomy using 20 human cadaveric leg dissections and report eight cases involving SPNAA-based perforator flap reconstructions (six propeller flaps and two free flaps) in a retrospective case series. Patient-specific baseline variables and intraoperative and postoperative outcomes are described. Results: Cadaveric dissection suggests that the location of the SPNAA is reliable but its origin varies, with 40% ( N = 8) of SPNAAs being of type I origin, 20% type II ( N = 4), and 40% ( N = 8) type III in our series. All reconstructions were successful. No intraoperative complications occurred during propeller or free-flap reconstructions. No flap failures occurred. One propeller reconstruction showed distal superficial skin necrosis and one donor site wound dehisced; both were successfully managed conservatively. No other short-term or long-term complications occurred. Conclusions: Flaps based on SPNAA perforators appear effective, reliable, and safe reconstructive methods for covering fibula osteocutaneous donor site defects and for intraoral reconstructions. Controlled trials are required to compare its effectiveness and safety with other reconstructive methods.